Comparison of Arabic Learning Outcomes through the Tarjamah Method - Ubay; Muh Jabir; Hakim, Mohamad Arfan; Nursyam; Umi Kalsum (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The main problem faced in the use of tarjamah method in Arabic language learning is the lack of mastery of mufradah and qawa'id, as well as the lack of listening, speaking, and writing skills. The purpose of this study was to determine and analyze the comparison of Arabic learning outcomes through the tarjamah method at Madrasah Aliyah Alkhairaat Palu and Madrasah Aliyah Negeri 1 Palu City. The research method used is quantitative by using data collection techniques in the form of observation and questionnaire. While the analysis techniques used are descriptive statistical analysis and inferential analysis. The results of hypothesis testing (one Sample T-test) showed sig.= 0.000 <0.05 which means there is a significant difference between the tarjamah method applied in class X Madrasah Aliyah Alkhairaat Pusat Palu and Class X Madrasah Aliyah Negeri 1 Palu City. The difference in the application of the tarjamah method has implications for students' learning outcomes, where the Arabic learning outcomes of Madrasah Aliyah Negeri 1 Palu City which adopts a more modern and contextual approach is higher than Madrasah Aliyah Alkhairaat Palu which tends to apply the tarjamah method conventionally with a more traditional approach. The results of this study confirm previous research that the use of the tarjamah method in Arabic language learning has a significant impact. In addition, this study also confirmed that the pedagogical approach used in the learning process has a direct impact on student learning outcomes.